The Phenomena of On-Street Parking at Kadipaten Traditional Market, West Java - Rahayu, Azi Juliar; Rifai, Andri Irfan; Akhir, Adinda Fajarika (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Congestion in Indonesia is a complex problem to overcome, caused by the large number of vehicles that are not matched by optimal road capacity and management. This often happens in community activity centers that are forced to park on the street with many vehicles that are not matched by optimal road capacity and management. This often happens in community activity centers that are forced to park on the street. This study aims to analyze the impact of on-street parking. The data was taken at the duchy's traditional market in West Java, Indonesia. The research method used is qualitative, carried out directly or through field surveys, referring to ICHM 1997. The results and conclusions show that on-street parking affects on-road performance in the Traditional Market Kadipaten.